Degree of Application of Reengineering in Government Schools in Northern West Bank Governorates from the Point of View Schools Principals - Nadia Murad Yosef Hannoun (My University, 2010)
This study sought to find out the degree of using the administrative engineering method in the practice administrative processes in public schools in the West Bank governorates as perceived by school principals of both sexes. In addition, the study examined the impact of variables of gender, academic qualification, administrative experience, school level, specialization and governorate on the responses of the school principals for the sake of finding out the extent of the use of the administrative engineering method in the practice of administrative processes in public schools in the West Bank governorates. The problem of the study was summed up in two questions: What is the degree of using the administrative engineering method in the practice of administrative processes in public schools in the West Bank governorates as perceived by school principals? Are there any statistically significant differences in the degree of using the administrative engineering method, in the practice of the administrative processes, which might be attributed to the variables of gender, academic qualification, administrative experience, school level, specialization and location of the directorate of education? To answer the questions of the study, the researcher developed a 35-item questionnaire and administered it to a random sample of 429 principals (28% of the population of the study).The first section of the questionnaire was devoted to a collection of primary data about the subjects. The second section had 35 items distributed among seven domains: planning in the light of administrative engineering, organization in the light of administrative engineering, orientation/guidance in the light of administrative engineering, follow up and evaluation in the light of administrative engineering, supervision in the light of administrative engineering, communication in the light of administrative engineering and decision making in the light of administrative engineering. The overall reliability coefficient of the instrument, using Cronbach’s alpha, was 0.909, and was appropriate enough for scientific research purposes.After data collection, the researcher conducted a statistical processing of data using arithmetic means , percentages, T-test for two independent groups, One- Way Analysis of Variance and Scheffe’s Test for multi – comparisons. After data analysis , the researcher found that the overall score of the degree of using the administrative engineering method in the practice of the administrative processes in public schools, as perceived by school principals, was very high (80.4%). The researcher also found no statistically significant differences at α = 0.05 in the degree of using the administrative engineering method in the practice of the administrative processes which might be attributed to the variables of gender , school level and specialization.However, it was found that there were statistically significant differences at α = 0.05 in the degree of using the administrative engineering method in the practice of the administrative processes in government schools which might be attributed to the academic qualification, in the planning domain, in favor of holders of postgraduate degrees. It was also found that there were statistically significant differences at α=0.05 in the degree of using the administrative engineering method in the practice of administrative processes in public schools which might be attributed to the variable of administrative experience in favor of those who had more than ten years of experience. In the light of the study findings, the researcher suggests the following recommendations: - Providing all elements and requirements necessary for the employment of the administrative engineering method in the practice of the administrative processes. - Embracing the administrative engineering method in the practice of the administrative processes in government schools and verifying the quality of these processes.

هدفت هذه الدراسة التعرف إلى درجة استخدام أسلوب الهندسة الإدارية في ممارسة العمليات الإدارية في المدارس الحكومية في محافظات الضفة الغربية، من وجهة نظر المديرين والمديرات ، بالإضافة إلى بيان أثر متغيرات الجنس، والمؤهل العلمي، والخبرة الإدارية، ومستوى المدرسة، والتخصص، والمحافظة، في استجابات المديرين والمديرات ، سعياً للوقوف على معرفة درجة استخدام أسلوب الهندسة الإدارية في ممارسة العمليات الإدارية في المدارس الحكومية في محافظات الضفة الغربية . وقد تحددت مشكلة الدراسة في الإجابة عن الأسئلة الآتية ما درجة استخدام أسلوب الهندسة الإدارية في ممارسة العمليات الإدارية في المدارس الحكومية في محافظات الضفة الغربية، من وجهة نظر المديرين والمديرات؟ هل توجد فروق في درجة استخدام أسلوب الهندسة الإدارية في ممارسة العمليات الإدارية في المدارس الحكومية في محافظات الضفة الغربية، من وجهة نظر المديرين والمديرات تبعاً لمتغير (الجنس، والمؤهل العلمي، والخبرة الإدارية، و مستوى المدرسة، والتخصص, وموقع المديرية)؟ ولتحقيق ذلك أجريت الدراسة على عينة متيسرة من المديرين والمديرات ، قوامها (429) تشكل ما نسبته (28 %) من مجتمع الدراسة، وقد تم جمع البيانات باستخدام استبانة تكونت من قسمين: القسم الأول، ويتضمن معلومات أولية، والقسم الثاني، و يشمل فقرات الاستبانة، وعددها (35) فقرة موزعة على سبعة مجالات هي: التخطيط في ضوء الهندسة الإدارية، والتنظيم في ضوء الهندسة الإدارية، و التوجيه في ضوء الهندسة الإدارية، و المتابعة والتقويم في ضوء الهندسة الإدارية، والرقابة في ضوء الهندسة الإدارية، و الاتصال في ضوء الهندسة الإدارية، واتخاذ القرار في ضوء الهندسة الإدارية. وقد بلغ معامل الثبات الكلي للأداة باستخدام معادلة كرونباخ ألفا إلى (0.909) فهي قابلة ومناسبة لأغراض البحث العلمي. وقد تم معالجة البيانات إحصائياً باستخدام المتوسطات الحسابية، والنسب المئوية، واختبار (ت) لمجموعتين مستقلتين، وتحليل التباين الأحادي، واختبار" شيفيه" للمقارنة البعدية. وتوصلت الدراسة إلى النتائج الآتية: - أن الدرجة الكلية لدرجة استخدام أسلوب الهندسة الإدارية في ممارسة العمليات الإدارية في المدارس الحكومية في محافظات الضفة الغربية، من وجهة نظر المديرين والمديرات، كانت مرتفعة جداً، إذ وصلت النسبة المئوية لاستجابة المبحوثين عليها إلى (80.4%). - لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة(0.05 = α) في درجة استخدام أسلوب الهندسة الإدارية في ممارسة العمليات الإدارية في المدارس الحكومية في محافظات الضفة الغربية، من وجهة نظر المديرين والمديرات، تعزى لمتغيرات الجنس، ومستوى المدرسة، والتخصص. - توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05 = α) في درجة استخدام أسلوب الهندسة الإدارية في ممارسة العمليات الإدارية في المدارس الحكومية في محافظات الضفة الغربية، من وجهة نظر المديرين والمديرات، وفق متغير المؤهل العلمي، في مجال التخطيط، ولصالح حملة مؤهل (أعلى من بكالوريوس). - توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05 = α) في درجة استخدام أسلوب الهندسة الإدارية في ممارسة العمليات الإدارية في المدارس الحكومية في محافظات الضفة الغربية، من وجهة نظر المديرين والمديرات، وفق متغير الخبرة الإدارية ولصالح (أكثر من 10 سنوات). وفي ضوء نتائج الدراسة، أوصت الباحثة بعدة توصيات أهمها: - ضرورة توفير جميع عناصر، ومتطلبات استخدام أسلوب الهندسة الإدارية، في ممارسة العمليات الإدارية. - ضرورة اعتماد أسلوب الهندسة الإدارية في ممارسة العمليات الإدارية في المدارس الحكومية، والتحقق من جودة العمليات الإدارية.
درجة تطبيق الهندرة في المدارس الحكومية في محافظات الضفة الغربية من وجهة نظر مديري المدارس ومديراتها